Seasonal growth of "algodão-bravo" (Ipomoea carnea spp. fistulosa) - Haase, Rainer (Pesquisa Agropecuaria Brasileira, 1999)
Ipomoea carnea spp. fistulosa, a native woody perennial, is capable of spreading rapidly over seasonally flooded grassland in the Brazilian Pantanal, South America's largest wetland, thus conflicting with the local cattle ranching. I. carnea is controlled by mowing at the onset of the rainy season, as close as possible before the seasonal flooding. Often, however, flooding begins after the plant has had enough time to re-sprout enabling it to survive. The objective of this study was to verify if Ipomoea carnea plant's production follows a seasonal cycle, and, if so, at which point in this cycle, the plant is most vulnerable to mechanical control measures. Seasonal dynamics of stem and leaf production of I. carnea were studied. The results showed that growth of I. carnea is fastest at the onset of the rainy season in November/December. Production declines when seasonal flooding commences in January/February and almost ceases towards the begin of the dry season in May/June. This leads to the proposal that I. carnea could be controlled more effectively if the weed were mown in the early dry season when its production and its capability to re-sprout is lowest, and if any new sprouts were cut by hand when the seasonal flooding starts.